The sustainability of a community pharmacy intervention to improve the quality use of asthma medication. - Bereznicki, B.; Peterson, G.; Jackson, S.; Walters, E. H.; Gee, P. (Journal of Clinical Pharmacy & Therapeutics, 2011)
A previously published asthma intervention used a software application to data mine pharmacy dispensing records and generate a list of patients with potentially suboptimal management of their asthma; in particular, a high rate of provision of reliever medication. These patients were sent educational material from their community pharmacists and advised to seek a review of their asthma management from their general practitioner. The intervention resulted in a 3-fold improvement in the ratio of dispensed preventer medication (inhaled corticosteroids) to reliever medication (short-acting beta-2 agonists). This follow-up study aimed to determine the long-term effects of the intervention programme on the preventer-to-reliever (P:R) ratio. The same data mining software was modified so that it could re-identify patients who were originally targeted for the intervention. Community pharmacists who participated in the previous intervention installed the modified version of the software. The dispensing data were then de-identified, encrypted and transferred via the Internet to a secure server. The follow-up dispensing data for all patients were compared with their pre- and post-intervention data collected originally. Of the 1551 patients who were included in the original study, 718 (46·3%) were eligible to be included in the follow-up study. The improved P:R ratio was sustained for at least 12 months following the intervention ( P < 0·01). The sustained increase in the P:R ratio was attributed to significant decreases in the average daily usage of reliever medication ( P < 0·0001). The follow-up study demonstrated a sustained improvement in the ratio of dispensed preventer medication to reliever medication for asthma. The intervention has the potential to show long-lasting and widespread improvements in asthma management, improved health outcomes for patients, and ultimately, a reduced burden on the health system.